Aligning Pancasila Values in The Regulation For Worship House Construction in Indonesia - Anifatul Kiftiyah; Tri Sutrisno (Badan Pembinaan Ideologi Pancasila, 2023)
Indonesia regulates the establishment of places of worship because its people adhere to different religions and beliefs, so it greatly influences the construction of the establishment of places of worship. The regulations for the construction of places of worship written in the Peraturan Bersama Menteri Agama dan Menteri Dalam Negeri (PBM) Nomor 9 and 8 Tahun 2006 are considered policies that discriminate against minorities. This research is a normative research with a juridical approach that uses the library research method to obtain valid sources as written references. The purpose of this research is that the regulations for the establishment of places of worship can be reviewed by synergizing Pancasila values ​​in them to avoid religious conflicts and for the sake of creating religious harmony. The conclusion of this study is that there are many cases of the construction of places of worship due to conditions that are considered discriminatory by minorities. So that this regulation needs to be reviewed by aligning the indicators of Pancasila values ​​based on the Badan Pembinaan Ideologi Pancasila Nomor 4 Tahun 2022 concerning Pancasila Indicators. Upholding Pancasila as grundnorm and staatfundamentalnorm means that all laws and policies must refer to Pancasila.